(untitled) (Research, Society and Development, 2023)
This work sought to describe the hospital mortality rate due to heart failure (HF) in the state of Sergipe, from 2010 to 2019. This is a descriptive, epidemiological, retrospective study, with secondary data collected at DATASUS. Hospital mortality due to HF was evaluated according to age group and sex. Descriptive statistics were used through means, absolute frequency, relative frequency and mortality rate. A pattern of reduction in the mortality rate was observed over the years, in 2010 the values were close to 9.15 and reduced to 7.46, totaling a reduction of 18.46%. Although the Sergipe population increased by 9.96%, there was a decrease in the number of hospitalizations evaluated at 30.54% and, consequently, a decrease in the number of deaths with 10.30%. When comparing these rates according to gender, it is noteworthy that higher mortality rates per year occur more frequently in the male population than in the female population, with an average of 7.98 and 7.42 respectively. In similar proportions there was an increase in the male population of 9.03% and female 10.85%, however, the reduction in female mortality was 29.32% and 5.20% in males. Relative increases in mortality rates were observed in the age groups from 60 years old, with a higher pattern of deaths as age advanced. Since Heart Failure is a disease with high morbidity and mortality, this study suggests a downward trend in the hospital mortality rate due to HF in Sergipe.